Rapid identification of Stenotrophomonas maltophilia by peptide nucleic acid fluorescence in situ hybridization. Issue 3 (25th March 2014) - Hansen, N.; Rasmussen, A. K. I.; Fiandaca, M. J.; Kragh, K. N.; Bjarnsholt, T.; Høiby, N.; Stender, H.; Guardabassi, L.
Abstract The objective of this study was to develop a novel peptide nucleic acid (PNA) probe for Stenotrophomonas maltophilia identification by fluorescence in situ hybridization (FISH). The probe was evaluated using 33 human and veterinary clinical S. maltophilia isolates and 45 reference strains representing common bacterial species in the respiratory tract. The probe displayed 100% sensitivity and 100% specificity on pure cultures and allowed detection in sputum from cystic fibrosis patients. The detection limit was 104 CFU/mL in spiked tracheal aspirate and bronchoalveolar lavage from healthy horses. Altogether the study shows that this species‐specific PNA FISH probe facilitates rapid detection of S. maltophilia in biological specimens.